Digger, dozer, dumper - Vestergaard, Hope; Slonim, David (Somerville, Massachusetts : Candlewick Press, 2013)
A treasury of sixteen poems highlights the jobs and personalities of an assortment of vehicles from an ambulance to a snowplow.
Keywords: Vehicles -- Juvenile poetry; Children's poetry, American; Vehicles -- Poetry; American poetry; Vehicles -- Poetry; Children's poetry